Implementasi Manajemen Strategik Dalam Peningkatan Mutu Pendidikan Di Lingkungan Fakultas Ekonomi Universitas Bangka Belitung - Indah Noviyanti; Ahmad Zohri Yanda; Amelia Patrina; Hansen Tandi; Marco Naibaho Hamonangan; Rohayati Rohayati; Wahyu Dwi Saputra Hadi; Veolen Veolen (Jurnal Mahasiswa Kreatif, 2023)
This study aims to determine the implementation process of strategic management in improving the quality of higher education at the Faculty of Economics, University of Bangka Belitung. This research uses descriptive method with quantitative approach. The population of this study were all students of the Faculty of Economics, Siliwangi University. The sample taken was 35 student representatives consisting of Management, Accounting, Economics, and Digital Business majors. Data collection was carried out by conducting observations and distributing questionnaires distributed using Google Form. The data collected is then processed by analysis. Based on the analysis and discussion that has been carried out, it can be concluded that the implementation of strategic management plays an important role in improving the quality of higher education at the Faculty of Economics, University of Bangka Belitung. The provision of facilities that support the administration and learning process, satisfying services, active participation of teaching staff and students, effective performance evaluation and control, and collaboration of all components are key factors in the implementation of strategic management.